La agroecología una alternativa para el desarrollo rural, casos San Pedro de Vilcabamba y Chuquiribamba de la provincia de Loja - Jaramillo Orosco, Jasenia del Pilar (2013)
Agro-ecology has been winning space in the field of rural development, as it has characteristics of clean and environmentally friendly production techniques, respecting individuals and organizations, partnerships among other networks of relationship, under a vision of complementarity for the integral development of the human being, the nature and mother Earth; which involves social, cultural, economic, productive and political aspects, taken into account in the National Plan of good living (Plan Nacional del Buen Vivir) However, the experiences in the agro-ecological system in the country and regional and, province level has not been consolidated either in the productive or at commercial level, which is mainly attributed to producers who have chosen the agro-ecology system do not have a local system of guaranty which acknowledges the quality of the products and therefore allows them compete in the market, in addition to the lack of programs and projects from the state which support agro-ecology, as an alternative to accomplish with the socio-economic development of producers dedicated to farming activity, and also the general population by contributing with healthy products which guaranty the food security and sovereignty. Before this problem, the research focuses its attention on the assessment of the social, economic and environmental impacts of the agro-ecological experiences in the parishes Chuquiribamba and San Pedro of Vilcabamba, then it evaluates the results in the process of agro-ecological transition, in which farms are currently working, and differentiates with the impact generated by the conventional or chemical production system, also compares the results obtained in the assessment of the two areas of study related to each other by the competitive and comparative differences in each zone. And based on this evaluation, other researches and bibliographic data, design a proposal that contributes to consolidate the productive and commercial processes of agro-ecology in the study cases of this paper. In order to accomplish the objectives of this research, interactive methodologies were applied: field visits, surveys, interviews, training workshops planned by the RAL, socialization meetings, and validation of results in which directors and producers participated, associated by the RAL, UNL, and GAD of Loja county, as actors involved in the process of territorial agro-ecological guaranty system. As response to this research work, it was possible to identify the relevant aspects and the positive impacts generated in the process of agro-ecological transition in the areas of study, referring to: increment of social and organization relationships, and exchange of experiences among agro-ecological producers in the same zone, and with other associations, strengthening of local capacities by training regarding the agro-ecology topic and collateral subjects, improvement of the diet in families and savings capacity due to self-consume of products from their farms, identification of profitability, and advances in the agro-ecological design of farms. Also the design of a proposal framed in action lines that involve production zones, products, organization, agents and commercial practices, and consumers; that allow contribute to consolidate the agro-ecology as an option for social and economic development of agro-ecological producers letting therefore to preserve the natural resources.